Sensitivity study of graphene nanoribbon with NH3 at room temperature - Hamidon, Mohd Nizar; Sim, Guan Ling; Usman, Kamilu Iman (Universiti Putra Malaysia Press, 2017)
This study presents the sensitivity of graphene nanoribbon (GNR) when exposed to ammonia gas at room temperature. Alumina were used as a substrate and coated with GNR as sensing film for ammonia gas detection. Four different concentration of GNR in the category of maximum, high, low, and minimum were prepared. Each category of GNR will be dispersed on alumina substrate with area of 1cm² and 4cm². 30nm of gold contacts are sputtered on both ends of the sensing film. The ammonia gas can be detected by measuring the changes in resistance. The GNR as ammonia sensor shows good responses at room temperature. In repeatability test, maximum GNR shows least variation when exposed to ammonia with the value of 1.01% (4cm²) and 2.12% (1cm²). In a sensitivity test, 0.25% to 1.00% of ammonia gas was used and tested on maximum GNR. Maximum GNR on 4cm² substrate shows higher sensitivity as compared to 1cm². Reaction time of GNR on ammonia gas decreased as the concentration of ammonia increased. Larger surface area of sensing element required lesser reaction time.